Spatiotemporal evaluation of PM2.5 concentration in Khuzestan province and examining the factors affecting it - kazem rangzan; Alireza Zarasvandi; mostafa kabolizadeh; shahin mohammadi; jasem mayahi (علوم محیطی)
Introduction: Particulate matters are one of the main air pollutants in urban areas, which are usually produced from various sources such as urban vehicles, fossil fuels, industrial activities. They may cause respiratory diseases, cardiovascular disease and death. It is, therefore, very important to be aware of spatial changes in these pollutants in areas with high levels of pollution. In this regard, the present study was conducted with the aim of spatio-temporal evaluation of the PM2.5 index in the period 1998 to 2016 in Khuzestan ProvinceMaterial and methods: For this study, first, precipitation, land surface temperature (LST), wind speed, Digital Elevation Model (DEM) and vegetation cover parameters were prepared using four satellites i.e. Terra, Landsat 8, SRTM and GPM, and ground data. Then PM2.5 index for four periods of 1998, 2004, 2010 and 2016 was extracted using satellite products for Khuzestan Province. Also, information on the distribution of the population and industries of the province was received from the relevant organizations. Finally, after providing the spatio-temporal changes of PM2.5 index in Khuzestan Province, the spatial changes of this index were studied with the mentioned parameters to evaluate the effect of each of these parameters on the contamination degree of this index.Results and discussion: The results of the present study showed that the southern cities of the province such as Mahshahr, Abadan and Shadegan are regions with higher potential in terms of particles smaller than 2.5 microns in size. The results of the study of population density and industries of this province showed that most of the cities in which the air pollution rate was high due to the PM2.5 index, had more industries and population density. The results also showed that in all study periods, in the northern and northeastern parts of the province, the amount of air pollution caused by this index was much lower than other regions of the province and the reason for this could be the low density of industries and population of these cities, among which we can mention the cities of Lali and Indika. In addition to the direct relationship between industry and human activities in increasing and decreasing the concentration of PM2.5 index, the relationship between this index and several factors (DEM, wind speed, precipitation, temperature and vegetation cover) was investigated. The correlation results between the mentioned parameters and PM2.5 concentration showed that the highest correlation was between PM2.5 concentration and precipitation and this relationship was inverse.Conclusion: It can be concluded that the concentration of PM2.5 pollutants in the southern and central areas is much higher than other areas and this could be due to the high density of power plants, industries and vehicle pollution in these areas‌. In addition, environmental and climatic factors can play an important role in the persistence and spread of the air pollution layer of this index. It should be noted that this research can be used as the basis for decision-making for air pollution management, which is an important step towards overcoming the crisis of air pollution.